Parasitic infections during pregnancy in Gabon affect glycosylation patterns of maternal and child antibodies - Yabo J. Honkpehedji; Anna O. Kildemoes; Koen A. Stam; Dieu L. Nguyen; Tom Veldhuizen; Angela van Diepen; Meral Esen; Peter G. Kremsner; Manfred Wuhrer; Ayôla A. Adegnika; Cornelis H. Hokke; Maria Yazdanbakhsh (Scientific Reports)
Abstract Antibody glycosylation patterns can affect antibody functionality and thereby contribute to protection against invading pathogens. During pregnancy, maternal antibodies can be transferred through the placenta and contribute to modulating both the mother’s and her child’s immune responses. Although several studies of IgG glycosylation during pregnancy have been carried out, very few cohorts studied were from sub-Saharan Africa, where exposure to microorganisms and parasites is high. In Lambaréné, Gabon, 106 pregnant women in their third trimester were enrolled into this study. At enrolment, urine, stool, and blood samples were collected from the mothers to assess Schistosoma haematobium (S. haematobium), Plasmodium falciparum (P. falciparum) and other parasite infections. During delivery, cord blood samples were collected. The children were followed, and blood samples were collected at 9 and 12 months of age. IgG Fc glycosylation was measured by liquid chromatography-mass spectrometry, determining fucosylation, galactosylation, sialylation, bisection, and sialylation per galactose (SA/gal). Among the 106 pregnant women, 33 (31%) were infected by at least one parasite. The antibody glycosylation patterns in maternal and cord blood showed distinct profiles when compared to that of infants at 9 and 12 months. IgG galactosylation was higher in maternal/cord blood, while fucosylated IgG was higher in children up to 1 year of age. Maternal parasitic infection was associated with lower IgG2 and IgG3/IgG4 galactosylation in cord blood and lower IgG3/IgG4 galactosylation in children. When maternal IgG galactosylation and, consequently, cord blood were categorized as high, children at 9 and 12 months of age showed higher IgG galactosylation compared to children of mothers with low IgG galactosylation. As IgG Fc galactosylation can have functional consequences, it might provide valuable information for developing effective preventive and treatment strategies for vulnerable populations.